Clinical Features, Treatment, and Outcomes Among Chinese Children With Anti-methyl-D-aspartate Receptor (Anti-NMDAR) Encephalitis - Zhang, Min; Li, Wenhui; Zhou, Shuizhen; Zhou, Yuanfeng; Yang, Haowei; Yu, Lifei; Wang, Ji; Wang, Yi; Zhang, Linmei (Frontiers in Neurology, 2019)
Objective: Anti-N- methyl-D-aspartate receptor (anti-NMDAR) encephalitis is the most common form of autoimmune encephalitis in pediatric patients. In the present study, we aimed to investigate the clinical features and long-term outcomes of pediatric patients with anti-NMDAR encephalitis in China. Methods: We conducted a retrospective study of children (age range: 0–18 years) with anti-NMDAR encephalitis treated at Children’s Hospital of Fudan University between July 2015 and November 2018. Demographic characteristics, clinical features, treatment, and outcomes were reviewed. Results: Thirty-four patients with anti-NMDAR encephalitis were enrolled (age range: 5 months to 14 years; median age: 7 years; female: 18). The median duration of follow up was 20 months (range: 6 to 39 months). Eighteen (52.9%) patients presented with seizure and 10(29.4%) with abnormal (psychiatric) behavior or cognitive dysfunction as the initial symptom. Thirty (88.2%) patients exhibited more than two symptoms during the disease course. No neoplasms were detected. Twelve (35.2%) patients had abnormal cerebrospinal fluid (CSF) findings, including exocytosis and increased protein concentration. Eighteen (52.9%) patients exhibited normal brain MRI findings. Electroencephalography revealed abnormal background in 27 (79.4%) patients, and 16 exhibited (47.0%) epileptiform discharges prior to immunotherapy. All patients received first-line immunotherapy, with 30 (88.2%) and four (11.8%) patients achieving good (Modified Rankin Scale [mRS] score of 0–2) and poor outcomes (mRS score of 3–5), respectively. Initial mRS scores differed significantly between the good and poor outcome groups. Fourteen out of 18 patients (77.7%) with seizure accepted anti-epileptic drug (AED) administration, and seizure freedom was achieved in 12out of 14 (85.7%) patients at the last follow-up. Ten of these 12 (83.3%) patients withdrew from AED treatment within 1 year. Conclusions: Seizure freedom was typically achieved, and our findings indicated that long-term use of AEDs may not be necessary. Among our patients, 83.3% were sensitive to first-line immunotherapy and achieved good outcomes. Higher mRS scores before immunotherapy predicted poor outcomes, highlighting the need for comprehensive assessment of anti-NMDAR encephalitis.